Readiness for Hospital Discharge and Its Correlation with the Quality of Discharge Teaching among the Parents of Premature Infants in NICU - Li Meng; Zhang Lingling; Zhang Haihong; Zhang Xiaobai; Huang Dandan; Wu Shaoyan (Applied Bionics and Biomechanics)
Objectives. To assess the extent of the readiness for hospital discharge and the correlation with discharge teaching quality among parents of premature infants’ in the NICU. Background. Low readiness for discharge from the hospital can lead to negative outcomes in healthcare for infants born prematurely and their parents. Discharge guidelines are a basic approach to ensure the readiness of the parents for discharge from the hospital. No investigation has ever been conducted into the sufficiency of hospital discharge guidelines for premature infants and their impact on parental readiness for hospital discharge. Design. Data was collected from four hospitals in China using a correlational descriptive study. Methods. Two hundred and eight parents of premature NICU-hospitalized infants of four tertiary hospitals in Henan Province from May to October 2020 were enrolled. The general information questionnaire, the readiness for hospital discharge scale- (RHDS-) parent form, and the quality of discharge teaching scale- (QDTS-) parent form were used for data collection. Spearman correlation analysis and descriptive statistics were used to analyze the data. Results. The total score for hospital discharge readiness was high (8.05±1.11). The total score of the quality of discharge guidelines was moderate (7.44±1.44). Moreover, the discharge teaching quality was positively correlated with the parents’ readiness. Positive correlations were found between PRHDS and QDTS subscales, including content received and delivery, physical-emotional status, knowledge, and expected support. Conclusion. The quality of the discharge guidelines perceived by parents of premature infants was moderate, which may have reduced their readiness for hospital discharge. Relevance to Clinical Practice. This study furnishes basic information on the importance of readiness of discharge for the parents of premature infants. The teaching guides nurses to enhance the quality of discharge teaching and the readiness of parents for discharge from the hospital.